2007
DOI: 10.1080/07481180701603394
|View full text |Cite
|
Sign up to set email alerts
|

A Chronological Perspective on Suicide—The Last Days of Life

Abstract: A combined psychological autopsy and narrative approach was used to study the completed suicides of 67 Israeli soldiers. Three issues were addressed. First, the authors examined the typology of the life narratives of suicide completed during active army duty. Second, focusing on the last 3 weeks of the soldiers' lives, they sought to examine their triggers for suicide, emotional state of mind, army duty functioning, and communication of suicidal intent. Finally, they examined military responses to communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
4
18
0
1
Order By: Relevance
“…This is in line with results reported by Orbach et al. () who postmortem investigated narratives covering the last 3 weeks of life of 67 Israeli soldiers who completed suicide. The authors found a split between an inner state of progressing emotional deterioration and simultaneously a mostly unimpaired outer appearance including behavioral military functioning, which was mostly stable.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in line with results reported by Orbach et al. () who postmortem investigated narratives covering the last 3 weeks of life of 67 Israeli soldiers who completed suicide. The authors found a split between an inner state of progressing emotional deterioration and simultaneously a mostly unimpaired outer appearance including behavioral military functioning, which was mostly stable.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, one may assume that an increased effort in trying to suppress and thus not overtly showing negative feelings was accompanied by an increase in suicidal ideation and the development of suicidal plans and behavior. The authors also point out that suppression of negative emotional states may be a distinct risk factor for suicidal behavior because it is accompanied by a resistance to receive help and thus impairs help allocation by professional services (Orbach et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of soldiers who died by suicide found that although many of these soldiers effectively maintained their military duties and expectations right up until death by suicide, they also demonstrated signs of emotional deterioration during the last days of their lives (Orbach et al, 2007). Thus, although a member of the military may appear to be functioning adequately, he or she may be masking suicidal ideation and preparation.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of psychological autopsy studies have been conducted with military samples, most of which are characterized by the inclusion of small samples (e.g., <40 cases), low response rates, and non-standardized assessment instruments, limiting the inferences that can be drawn from the results of these studies (Dedic and Panic, 2010, Farberow et al, 1990, Orbach et al, 2007). Moreover, many prior psychological autopsy studies have used either no control condition, or have included as controls people who have died from other causes (e.g., accidents, natural death), or people with a psychiatric disorder (Cavanagh et al, 2003).…”
mentioning
confidence: 99%